The Effect of Service Quality Price and Infrastructure Facilities on Customer Satisfaction at The Main Clinic of Balai Kesehatan Kerja Pelayaran - Hutapea, Rita Novery; Sundari, Sri (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study analyses customer satisfaction at the Main Clinic of Balai Kesehatan Kerja Pelayaran, the data shows that the customer satisfaction target has not been achieved optimally with the target to be achieved index 100 and scale 4 currently still at 85.55 and scale 38.33. Therefore, this study aims to measure the effect of price, service quality and infrastructure facilities on customer satisfaction at the Main Clinic of Balai Kesehatan Kerja Pelayaran. Researchers also gave questionnaires to 85 patients, this questionnaire as a means of collecting information data related to price, service quality, infrastructure and customer satisfaction. Based on the results of data processing using the SPSS statistical programme vers. 21 and obtained the results of price variables (X1), service quality (X2), infrastructure facilities (X3) together have a positive and significant effect on customer satisfaction (Y). The test results indicated by the Fcount value is 54.616 and a significant level of 0.000 while the Ftable value is 1.663. Due to the Fcount value of 54.616 greater than the Ftable value of 1.663 and a significant level of 0.000 while the value is smaller than the significance probability of 0.05, Ho is rejected and H1 is accepted, so it can be concluded that the variables of price, service quality and infrastructure together have a positive and significant effect on customer satisfaction and the magnitude of the influence of the variables is 65.7% is customer satisfaction and the remaining 34.3% is influenced by other variables not included in the study.